Democratic electoral systems and the environment of the developing world - Gan, Damian Zheing Weii (2018)
Are some electoral systems more competent at environmental protection than others? This study proposes and empirically tests causal linkages between the electoral systems, economic performances, and levels of environmental degradation of developing democracies. Two sets of time-series cross-sectional multivariate regression analyses (i.e., econometric and environmental degradations) were conducted using a sample of 40 developing democracies, from the time period of 1995-2015. The findings suggest that majoritarian systems have more dynamic economic performances compared to proportional representation (PR) systems. Furthermore, majoritarian systems emitted significantly more carbon dioxide and produced worse Environmental Performance Index scores. I argue that the higher levels of environmental degradation of majoritarian systems relative to PR systems can be partially attributed to their more robust economic activities. At the same time, majoritarian systems produced surprisingly lower levels of sulfur dioxide pollution compared to PR systems. I show that there is sufficient evidence to challenge the conventional wisdom that PR systems are systematically better at offering environmental protection.